An update on head and neck squamous cell carcinoma in respect to classification and systemic therapy. Extended review - A. Mudunov; A. Ahundov; M. Bolotin; T. Braunschweig (Опухоли головы и шеи)
Head and neck squamous cell carcinoma (HNSCC) is among the 10 most common cancers and demonstrates high mortality rates. Well known for its relation to smoking and alcohol consumption, in within the past 10 years a high number of cases, especially of the oropharynx could  be shown to be based on an infection of human papilloma virus, high risk subtypes, mostly type 16 and 18. Often it is connected to younger age at onset, better outcome and better response to radiochemotherapy.Next to well established radiochemotherapy schemes, including targeted therapy as cetuximab, in the recent 2 years a complete new therapeutic approach manifested, called checkpoint inhibition. The drugs of this class block a binding of a membranous ligand to a surface receptor  on T-cells. Without blocking, this binding is physiological in antigen-presenting cells or many other normal tissue cells (e.g. heart muscle, trophoblast) inhibiting activation of the cytotoxic T-cells. Research revealed an identical way of tumor cells escaping cell death caused  by patient’s own immune system. By blocking this inhibition, in several carcinoma entities, a very effective disease control was achieved.  So far, 2 pairs of binding are approved for treatment: CD80-CTLA4 and PD1-PDL1. In CD80-CTLA4, it is an inhibitor to CTLA4 (e. g. Ipilimumab), in PD1-PDL1, for both, the ligand an receptor are several inhibitors on the market (e. g. Nivolumab, Pembrolizumab, Atezolizumab, Durvalumab). So far, there could not be found a highly predictive marker for the grade of efficiency of these inhibitors. Next  to very recent and complex markers, tumor mutational burden, the immunohistochemical staining for the ligand, PD-L1 could be established in a few number of carcinoma, incuding adenocarcinoma of the lung. Next to different ways of interpretation of the staining, also different staining procedures used in the trials are hindering an easy establishment of this marker in pathology laboratories. The staining procedures used in trials are not comparable with common immunohistochemistry due to very high costs of reagents (test-kits sold by the involved companies, so called companion diagnostic). To overcome these drawbacks, different studies were performed comparing the different antibody clones  of immunohistochemical stains used in the official trials and antibodies of other companies. These harmonization studies brought to light that most antibodies stain equally, even the antibodies available from other companies thus making this stain more effordable and possible  for introduction in the marker-portfolio of labs of pathology.In HNSCC there is a better response to checkpoint inhibitors in cases of high PD-L1 expression, but also in negative cases, an effect could  be seen. The actual approval are exclusively for patients in second line without PD-L1 testing. Upcoming approvals for first line treatment  by checkpoint inhibitors are likely to include immunohistochemical testing for PD-L1.